Molecular Docking Human Plasma Kallikrein to Prevent Acute Respiratory Distress Syndrome(ARDS) in COVID-19 Patient - Feriawan Tan; Cindy ApriliaEkaPrasanty; Anna Surgean Veterini; YuaniSetiawati; Rizki Awaluddin; Fadilah Fadilah; Siti Khaerunnisa (Indian Journal of Forensic Medicine & Toxicology, 2021)
SARS CoV-2 infection causes various clinical manifestations ranging from mild to severe. Acute RespiratoryDistress Syndrome (ARDS) is a severe complication of COVID-19 caused by activation of the kallikreinkininsystem which produces bradykinin which is a potent proinflammatory mediator. This research is anin silico study which aims to determine the potential of active medicinal plant compounds in inhibiting thekallikrein-kinin system.Molecular docking in this study using Autodock 4.2 with Lamarckian GA criteria.Human plasma kallikrein (PDB ID: 5TJX) was docked with 70 compounds and one native ligandand analyzedusing Autodock 4.2.The smallest binding energy obtained from docking 5TJX with several compoundsin sequence, namely, xanthohumol, nafamostat, demethoxycurcumin, epicatechingallate, beta mangostin,alpha mangostin (-9.52, -9.35, -9.33, -9.28, -9.19, -9.06 kcal/mol). Therefore, the compound shows the bestpotential as a plasma kallikrein inhibitor. However, further research is still needed to determine the potentialof drugs and medicinal plant active compounds for medical treatment.